The Violation of the Laws of Armed Conflict in the Ukrainian and Polish Dimension: The Criminal Law Discourse - Sotula, Oleksandr (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The current Criminal Code of Ukraine has shown that it can effectively respond to the challenges associated with the war unleashed by the Russian Federation against Ukraine. Chapter XX of the Special Part of the Criminal Code of Ukraine contains a number of articles that qualify the criminal acts of Russian occupiers. First of all, this is Article 438 “Violation of the laws and customs of war”. In its content, it largely reflects the compliance of Ukrainian national criminal law with the provisions of international law in the field of the regulation of responsibility for committing criminal violations of international humanitarian law (the law of armed conflicts). A comparative legal analysis of Ukrainian and Polish legislation was carried out in terms of criminal liability for the violation of the laws and customs of war. Criminal violations of international humanitarian law are punishable under Articles 122–126 of the Criminal Code of the Republic of Poland. A detailed analysis of the content of these articles of the Criminal Code of the Republic of Poland showed a significant difference between the norms of the Polish criminal law in terms of detailing the acts that the Polish legislator defined as a violation of international humanitarian law. In particular, in addition to the general concept of the civilian population, the Polish criminal law proposes as victims persons laying down their arms or having no means of protection, the surrendered, the wounded, the sick, the shipwrecked, medical personnel, the clergy, unifying the concept of all persons enjoying international protection during armed hostilities. This position of the Polish legislator is more constructive and more closely connected with the relevant international legal acts than the corresponding norm of the Criminal Code of Ukraine. In addition, § 2 of Article 123 of the Criminal Code of the Republic of Poland provides an expanded understanding of ill-treatment of victims, which is not found in Article 438 of the Criminal Code of Ukraine. Also, the Ukrainian legislator ignored those violations of international humanitarian law which are indicated in Article 124 of the Criminal Code of the Republic of Poland – which also works in favour of the Polish criminal law, as it tries to comply with the provisions of international humanitarian law to a greater extent.